Seed yield variables of five wild Poaceae species in La Siberia, Chapingo, México (Agro Productividad, 2022)
The objective of the study was to evaluate the seed yield variables in situ in Bouteloua gracilis, Bouteloua hirsuta, Bouteloua curtipendula, Mulhenbergia rigida and Schizachyrium scoparium in La Siberia, Chapingo, Mexico. The study was carried out on wild plants in which the following were recorded: total stems plant-1, number of branches plant-1, number and quantity of seed-1, stem-1 and plant- 1 to later evaluate the percentage of filling and viability. The data were analyzed with GLM of SAS in Completely Random Blocks design and Tukey’s test (α = 0.05). There was no grass species that exceeded 25 flower stems per plant (P